Analisis Perkembangan Sosial Emosional Anak Usia Dini pada Permainan Tradisional Congklak di Kelompok B TK Al Ikhlas 01 Sambong Batang - Sugiyanti, Sugiyanti; Buchori, Achmad; Sulianto, Joko (Universitas PGRI Semarang, 2023)
Early childhood education at the age of 0-6 years is known as the Golden Age period. This period that only lasts once in each individual's lifetime can have an influence on the next stage of growth and development. So it is necessary to provide appropriate stimulation, one of which is to stimulate social emotional development. Social emotional development can be improved by playing traditional congklak games. In this study, it aims to provide an overview of traditional games in early childhood and determine the increase in social emotional development in early childhood through playing traditional congklak games and knowing the factors that influence early childhood social-emotional development when doing traditional congklak games. The method in this study is included in the type of field research (field research) and in terms of the type of data collected is included in qualitative approach research. The study was conducted in a natural setting in group B of TK Al-Ikhlas 01 Sambong Batang. Data mining is carried out using three main methods, namely in-depth observation, , interviews and documentation. Early childhood social emotional development in group B of TK Al Ikhlas 01 Sambong Batang before going through the traditional game of congklak there were 7 children who were not yet developed (BB), 15 children began to develop (MB), 3 children developed as expected (BSH). However, after going through the traditional game of congklak began to be seen and improved, there were 6 children starting to develop (MB), there were 14 children developing as expected and 5 children developing very well (BSB). The effectiveness of learning using traditional congklak games in early childhood social-emotional development in group B of TK Al Ikhlas 01 Sambong Batang is very effective to use. When playing congklak, students hone patience, train confidence in making decisions, be responsible in carrying out tasks, train children to be more independent and not dependent on others and train self-management behavior in children. Factors that influence the social emotional development of early childhood in traditional congklak games are general factors that are divided into maturity factors which are classified as heredity factors and learning environment.